Open hand, closed fist : practices of undocumented organizing in a hostile state - Abrams, Kathryn (University of California Press, 2022)
"How does a group that lacks legal status organize its members to become effective political activists? In the early 2000s, Arizona's campaign of "attrition by enforcement" aimed to make life so miserable for undocumented immigrants that they would "self-deport." Undocumented activists resisted hostile legislation, registered thousands of new Latino voters, and joined a national movement to advance justice for immigrants. Drawing on five years of observation and interviews with activists in Phoenix, Arizona, Kathryn Abrams explains how the practices of storytelling, emotion cultures, and performative citizenship fueled this grassroots movement. Together these practices produced both the "open hand" (the affective bonds among participants) and the "closed fist" (the pragmatic strategies of resistance) that have allowed the movement to mobilize and sustain itself over time. "--